Acute and chronic toxicity of lindane on Ceriodaphnia cornuta (Cladocera: Daphniidae) - Juárez, Jorgelina (2010)
Lindane is an organochlorine pesticide toxicity which produces harmful effects on human health and biota. The aim of this study was to evaluate the acute and chronic toxicity of Lindane on microcrustaceans Ceriodaphnia cornuta. For acute tests used a static design, using 10 infants ≤ 24 hours of age for control and each concen- tration of lindane (5, 10, 15, 20 and 25 mg/L). There were three replicates of each treatment. Monitored the detention of individuals at 48 am and calculated LC50 values. Chronic Bioassays consisted of a semi-static design, using 10 infants ≤ 24 hours of age (one per vessel) for the control and each of the toxic sublethal concentration (0.1, 0.15, 0.2, 0.25 and 0.3 mg/L). The effects on survival and reproduction over 21 days. The LC50 value of 48 hours was 5.293 ± 0.7 mg/L. Reproductive parameters (neonates per female, litter size and rate of natural increase) decreased with increasing concentration of toxic evaluated, while the onset of sexual maturity is delayed, thus demonstrating the sensitivity of test organisms to lindane.